Federalismo e autogestão: anarquismo - Proudhon, guerra civil espanhola - Montebello, Natalia Monzón (2009)
The notions of federalism and self-management are used composing a analytic point of view on experimentation in the Pierre-Joseph Proudhon and the Spanish Civil War. The analytic experimentation Policy propose questions that provoke conversation today with Gilles Deleuze, Michel Foucault and Nietzsche Friedich, as well the presence of Federico García Lorca. It is dissolving the identity, philosophy and history, out of play of the identity. In Proudhon, the serial analitic unfolds in decentralized federalism articulated to mutualism, as sliding out of State, that not only dispenses with the formality intitucional, as well as state form as well as of thought. Thus, the interruption of the centrality and the hierarchy of State describes in the anarchism the affirmation of freedom practices and free lifestyle of the sovereign. The anarchism don t happens as the oppositions to the State, but as invention of exist-rience free absolute authority, projecting itself as a multiplicity of partnerships, in the coexistence of the differents in equality. In the Spanish Civil War, the invention of freedon practices settles in the nineteenth century as social revolution that subervert the politic and economic fields demarked on the struggles of workers